Entrepreneurial orientation: International, global and cross-cultural research. (March 2019) - Wales, William; Gupta, Vishal K; Marino, Louis; Shirokova, Galina
The last few years have witnessed a significant increase in academic research examining entrepreneurial orientation (EO), with scholarship on this topic being regularly published internationally. This special issue addresses the need to develop a deeper understanding of EO in the global context. Globalisation and the growing popularity of entrepreneurship worldwide have motivated interest in understanding the manifestation and application of EO in diverse socio-cultural contexts. It is our hope that this special issue helps illuminate and advance important areas of study in the international and cross-cultural EO literature, especially those that have remained under-examined thus far. We believe that the impact of future research on EO within international contexts depends upon the ability of the scholars to build upon past research. As it happens, this special issue is a celebration of the 30-year anniversary of the foundational work of Covin and Slevin that paved the way for the systematic investigation of EO.